INDIA AND THE CARTAGENA CONFERENCE - Kumar, Vinod (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The present research paper evaluates the Cartagena (1995) Conference of the Non-Aligned Movement. Through the conference, an attempt is also made to clarify what kind of role India played in this conference. New programs were approved in the final declaration of this conference. 64 point proposals were accepted in a special meeting of member countries. And along with this, this conference was also important because the member countries outlined their economic priorities for the first time. The leaders were of the view that after getting rid of the political tensions before the Cold War, dialogue should be promoted among the developing countries to fulfill the commitment of the Non-Aligned Movement to eradicate illiteracy and poverty. This research paper is also published in International Journal of Advanced Research and Development, July 2016.